2017
DOI: 10.1093/mspecies/sex011
|View full text |Cite
|
Sign up to set email alerts
|

Myotis riparius (Chiroptera: Vespertilionidae)

Abstract: Abstract:Myotis riparius is a vespertilionid bat commonly called the riparian myotis. It is a medium-sized bat, with woolly fur; color of dorsal fur varies geographically from a reddish to blackish tinge. M. riparius is widely distributed in the Neotropics, occurring from Honduras southward into South America to Paraguay, northern Argentina, and Uruguay. It occurs in rainforests, savannas, and open habitats, at elevations from sea level to about 2,000 m. It is listed as "Least Concern" by the International Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 486 publications
(18 citation statements)
references
References 24 publications
3
15
0
Order By: Relevance
“…Myotis riparius occurs in varied environments, from open and forested habitats to altered areas, undergoing large habitat plasticity (Novaes et al 2017). The capture of the individual in the Reserva Particular do Patrimônio Natural do Caju, in an area associated with bodies of water, corroborates that reported by other studies, as this species is usually found in humid forested areas, forag-ing in environments close to water sources (e.g.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Myotis riparius occurs in varied environments, from open and forested habitats to altered areas, undergoing large habitat plasticity (Novaes et al 2017). The capture of the individual in the Reserva Particular do Patrimônio Natural do Caju, in an area associated with bodies of water, corroborates that reported by other studies, as this species is usually found in humid forested areas, forag-ing in environments close to water sources (e.g.…”
Section: Discussionsupporting
confidence: 86%
“…The specimens in Sergipe presented a forearm length at 34.19 mm (to CMUFS 291) and 35.90 mm (CMUFS 145) and is in agreement with reported measurements, for example, by Vicente et al (2005), Dias and Peracchi (2007) between the breadth across the canines and the postorbital constriction is over 1.0 (1.06), diagnostic features reported by López-González et al (2001) and Dias and Peracchi (2007). Other body and cranial measurements were similar (Table 1) to those reported by Simmons and Voss (1988), Lim et al (1999), López-González et al (2001, Dias and Peracchi (2007), and Novaes et al (2017).…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Myotis riparius Handley, 1960 Handley (1960), LaVal (1973, Simmons andVoss (1998), Brosset andCharles-Dominique (1990), Lopez-Gonzalez et al (2001), Moratelli et al (2013), andNovaes et al (2017). No subspecies are currently recognized in M. riparius (Novaes et al, 2017).…”
Section: Myotis Caucensis Allen 1914mentioning
confidence: 99%
“…Myotis riparius Handley, 1960 Handley (1960), LaVal (1973, Simmons andVoss (1998), Brosset andCharles-Dominique (1990), Lopez-Gonzalez et al (2001), Moratelli et al (2013), andNovaes et al (2017). No subspecies are currently recognized in M. riparius (Novaes et al, 2017). Our Mayo River basin voucher speci¬ mens exhibit the diagnostic characteristics of the species: fur long and woolly; dorsal pelage unicol¬ ored; plagiopatagium attached to the foot at the level of the base of the toes; a fringe of hairs lack¬ ing along the trailing edge of uropatagium; sagittal and lambdoidal crests present; and occipital region flattened posteriorly (Novaes et al, 2017).…”
Section: Myotis Caucensis Allen 1914mentioning
confidence: 99%